Effects of Federal Support on Company-Financed R and D: The Case of Energy - Mansfield, Edwin; Switzer, Lorne (Management Science, 1984)
For decades, policy makers in both the public and private sectors have been concerned with the question: What is the impact of changes in federal R and D support on company-financed R and D expenditures? This is one of the first empirical studies at a micro level of this topic. The results, which pertain to energy R and D, indicate a complementarity between government-financed and company-financed R and D, on the average, although there is a considerable amount of interfirm variation in this regard. In about one-third of the projects studied, federally-financed R and D projects suggested some further R and D into which the firm invested its own funds. The results of a logit analysis suggest that whether or not a government-financed R and D project results in such a spinoff depends on the extent to which the performing firm contributes to the formulation of the project’s goals and strategies.